Niosomes as Efficient Nanocarriers for Targeted Drug Delivery - Kapoor, Anupriya (Asian Journal of Pharmaceutics (AJP), 2024)
The localization of pharmacological molecules to stick locations is made possible by target-specific drug delivery systems with its bi-layer structure made of non-ionic surfactants, the noisome vesicular system can temporarily increase a drug’s bioavailability in a specific location. Scientists who study drug delivery systems have been highly concerned with the creation of vesicles as a means of enhancing medication delivery in recent years. Niosomes’ amphiphilic character enhances their ability to effectively encapsulate hydrophilic or lipophilic medications. It is common practice to add additional ingredients, like cholesterol, to preserve the niosomes’ structural stiffness. When comparing the great chemical stability and effectiveness of the replacement with niosomes, liposomes use vesicles for medicinal and therapeutic applications, which have several advantages. They boost the therapeutic efficiency of drug molecules by keeping the medicine from exiting circulation too quickly, shielding it from its genetic environment, and lessening its effect on target cells. This research concentrated on current advancements in the distribution of niosomal medications, potential advantages over other delivery systems, building techniques, characterization techniques, and recent research that is noisy. The use of niosomes in nanotechnology has the potential to yield highly targeted, non- infective, and non-cancer agents. Proniosomes and aspasomes are a few examples of novel concepts that have been used to enhance niosomes’ drug delivery capabilities. Niosomes are also beneficial as a living component of vaccines and for diagnostic tests. Therefore, further research and development are required in these areas to produce the niosomal preparations that are now on the market.